Dihydroartemisinin, a potential PTGS1 inhibitor, potentiated cisplatin-induced cell death in non-small cell lung cancer through activating ROS-mediated multiple signaling pathways - Ni, Lianli; Zhu, Xinping; Zhao, Qi; Shen, Yiwei; Tao, Lu; Zhang, Ji; Lin, Han; Zhuge, Weishan; Cho, Young-Chang; Cui, Ri; Zhu, Wangyu (Neoplasia (New York, N.Y.), 2024)
•Combined therapy with DHA and cisplatin exerts synergistic anti-NSCLC activity through activating ROS-mediated ER stress, JNK and p38 MAPK signaling pathways both in vitro and vivo.•PTGS1 is identified as a potential novel target of DHA. Knockdown of PTGS1 enhanced DHA-induced cell death in NSCLC cells through stimulating ROS-mediated ER stress, JNK and p38 MAPK signaling pathways. Dihydroartemisinin (DHA) exerts an anti-tumor effect in multiple cancers, however, the molecular mechanism of DHA and whether DHA facilitates the anti-tumor efficacy of cisplatin in non-small cell lung cancer (NSCLC) are unclear. Here, we found that DHA potentiated the anti-tumor effects of cisplatin in NSCLC cells by stimulating reactive oxygen species (ROS)-mediated endoplasmic reticulum (ER) stress, C-Jun-amino-terminal kinase (JNK) and p38 MAPK signaling pathways both in vitro and in vivo. Of note, we demonstrated for the first time that DHA inhibits prostaglandin G/H synthase 1 (PTGS1) expression, resulting in enhanced ROS production. Importantly, silencing PTGS1 sensitized DHA-induced cell death by increasing ROS production and activating ER-stress, JNK and p38 MAPK signaling pathways. In summary, our findings provided new experimental basis and therapeutic prospect for the combined therapy with DHA and cisplatin in some NSCLC patients. [Display omitted]